Analisis Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Nasabah Bumdes Desa Wonoasri Kabupaten Jember - Auliannisa Vistya Dianty; Trias Setyowati; Tatit Diansari Reskiputri (Universitas Muhammadiyah Gresik, 2021)
Background - Efforts to improve service quality are very influential on the future of a company to foster trust and provide satisfaction to customers or consumers. Objective - This study aims to determine how influential the service quality variables consisting of tangibles, responsiveness, reliability, assurance and empathy and the trust variables consisting of ability, benevolence, integrity on customer satisfaction BUMDes Dana Asri Sejahtera. Design/Methodology/Approach - This research is causal associative research using quantitative technique. The data used in this study are primary data and secondary data, with a sample of 85 people. Findings – Based on the results of the calculation of multiple linear regression analysis on the service quality variable, the most influential dimension is tangibles with a total of 1,264, while the most influential dimension of trust is ability with a total of 1.132. So the conclusion obtained is that the variables of service quality and trust have a significant effect simultaneously and partially on customer satisfaction. Research implications - The results of this study have the implication that customer satisfaction can be increased through improving service quality and customer trust and can be a reference for the influence of service quality and trust on satisfaction, especially for BUMDes Dana Asri Sejahtera customers. Research limitations - The limitations of this study are the number of respondents, which is only 85 people, of course, is still lacking to describe the real situation and the information provided by respondents through questionnaires sometimes does not show the actual events, because sometimes it is caused by differences in thoughts, assumptions and understandings of each respondent.